Genomewide gene‐associated microsatellite markers for the model invasive ascidian, Ciona intestinalis species complex. (19th November 2015) - Lin, Yaping; Chen, Yiyong; Xiong, Wei; Zhan, Aibin
Abstract: The vase tunicate, Ciona intestinalis species complex, has become a good model for ecological and evolutionary studies, especially those focusing on microevolution associated with rapidly changing environments. However, genomewide genetic markers are still lacking. Here, we characterized a large set of genomewide gene‐associated microsatellite markers for C. intestinalis spA (= C. robusta ). Bioinformatic analysis identified 4654 microsatellites from expressed sequence tags (ESTs), 2126 of which successfully assigned to chromosomes were selected for further analysis. Based on the distribution evenness on chromosomes, function annotation and suitability for primer design, we chose 545 candidate microsatellites for further characterization. After amplification validation and variation assessment, 218 loci were polymorphic in at least one of the two populations collected from the coast of Arenys de Mar, Spain ( N  =   24–48), and Cape Town, South Africa ( N  =   24–33). The number of alleles, observed heterozygosity and expected heterozygosity ranged from 2 to 11, 0 to 0.833 and 0.021 to 0.818, and from 2 to 10, 0 to 0.879 and 0.031 to 0.845 for the Spanish and African populations, respectively. When all microsatellites were tested for cross‐species utility, only 60 loci (25.8%) could be successfully amplified and all loci were polymorphic in C. intestinalis spB. A high level of genomewide polymorphism is likely responsible for the low transferability. The large set of microsatellite markers characterized here is expected to provide a useful genomewide resource for ecological and evolutionary studies using C. intestinalis as a model.